2011
DOI: 10.1002/ajim.21004
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk in the electroplating industry in Lombardy, Italy, using the Italian occupational cancer monitoring (OCCAM) information system

Abstract: Electroplaters had higher risks than "metal treatment" workers. Although the risks were due to past exposure, case histories and recent acute effects indicate a present carcinogenic hazard in some Lombardy electroplating factories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
(7 reference statements)
0
11
1
Order By: Relevance
“…However, unlike the decision latitude items, there was no clear pattern in bivariate differences observed in responses to individual items. For example, although previous research suggests that individuals with higher levels of education report greater psychological demands (see Landsbergis et al [1] for review), we did not observe a consistent pattern for those responding ‘very often’ or ‘always’ for the two job demands items. Although ‘Job requires working hard’ had a higher percentage of farm workers with 10 or more years of education, this did not hold for the second job demands item.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…However, unlike the decision latitude items, there was no clear pattern in bivariate differences observed in responses to individual items. For example, although previous research suggests that individuals with higher levels of education report greater psychological demands (see Landsbergis et al [1] for review), we did not observe a consistent pattern for those responding ‘very often’ or ‘always’ for the two job demands items. Although ‘Job requires working hard’ had a higher percentage of farm workers with 10 or more years of education, this did not hold for the second job demands item.…”
Section: Discussioncontrasting
confidence: 95%
“…Although there have been some applications of the demands-control model to health-related outcomes among immigrant workers [9, 21], the widespread application of this popular model remains encumbered by the absence of careful measurement evaluation. Indeed, in their recent summary of the literature, Landsbergis et al [1] reported that measurement evaluation of common instruments in the occupational stress literature is an essential step in advancing understanding of occupational health disparities. This study was designed to meet that call, and in doing so it makes two primary contributions to the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A record linkage is carried out between the regional databases of hospital discharge records, through which cancer cases are identified, and the archives of pension funds at the National Institute for Social Security (INPS), which records the occupational history of every person who worked in private enterprises since 1974. This approach has been used to conduct several population‐based case–control studies [Aiani et al, ; Panizza et al, ] and may be used to analyze virtually any association between trades and cancer sites [Crosignani et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…The most serious adverse health effects due to occupational exposure to nickel and its compounds are lung fibrosis and lung cancer, nickel is also hematotoxic, hepatotoxic and nephrotoxic. Allergic skin reactions are relatively common in individuals who are exposed to nickel (Brüske-Hohlfeld, 2009;Das & Buchner, 2007;Panizza, 2011;Zhao, 2009 (Morimoto et al, 2010). Cytokine-induced neutrophil chemoattractant-1 (CINC-1), CINC-2 alpha, beta, and CINC-3 were involved in the persistent pulmonary inflammation by NiO NP ) but NiO NP did not induce the gene expression of MMP-2 and TIMP-2 mRNA in rat lungs .…”
Section: Nio Nanoparticlesmentioning
confidence: 99%